Genome-wide association mapping for root traits associated with frost tolerance in faba beans using KASP-SNP markers - Sallam, Ahmed; Moursi, Yasser S.; Martsch, Regina; Eltaher, Shamseldeen (Frontiers in Genetics, 2022)
Frost is abiotic stress that threats plant development and crop productivity not only in cold regions but also in temperate zones. Vicia faba L. is the fourth legume crop in terms of productivity. Albeit its wide adaptability to a wide range of habitats compared to other legume crops, it shows susceptibility to some abiotic stresses such as sub-zero temperatures. Winter faba bean varieties are more productive than the spring varieties. Frost seriously decreases plant growth and productivity by destroying the fine roots. As yield is the main target of breeders, in couple with the challenge of precisely measuring the root-related traits, much more attention has been paid to the aboveground organs. Maintaining, healthy roots under harsh growth conditions is pivotal for plant growth sustaining. Thus, the current study deals with identifying the genomic regions that control the frost tolerance in a winter faba bean population, focusing on root-related traits. A set of 185 genotypes were tested for frost tolerance under artificial frost growth conditions in a growth chamber. The frost stress reduced the root-related parameters in all genotypes, showing wide variations among the genotypes. The heritabilities of the root-related traits were relatively high. All root related-traits showed high positive correlations. However, the correlations with the shoot-related traits were negative or weak. The Genome-wide association scan (GWAS) revealed novel nine SNPs that are associated with the root-related traits. The most frost-tolerant genotypes were detected; the two genotypes; S_028 and S_220 exhibited remarkable performance under frost stress. Moreover, they are harboring four out of the four favorable alleles for frost tolerance. Both parents can be implemented in a breeding program to develop more frost-tolerant varieties. These results could provide new insights for improving frost tolerance not only in faba bean but also in the other legume crops.